Clinical Profile, Drug Utilization Pattern and Adverse Drug Reactions of Anti-tubercular Drugs at DOTS Center in a Tertiary Hospital - Chaudhary, Aswani; Sarraf, DP; Bhattarai, NR; Chaudhary, A; Rauniar, GP (Nepal Medical College Journal, 2020)
Most of anti-tubercular drugs (ATD) cause various adverse drug reactions (ADRs) leading to significant morbidity which may have negative consequences on drug adherence and treatment outcome. The objectives of the study were to know the clinical profile of patients receiving ATD, to identify the pattern of ADRs caused by ATD and to know the drug utilization pattern (DUP) in different types of tuberculosis (TB). A prospective observational study was conducted among patients diagnosed with TB at DOTS center in BPKIHS from June 2017 to May 2018 and occurrence of any ADRs were detected during their monthly visit. Descriptive statistics were used to analyze the data. A total of 126 tuberculosis patients were on ATD therapy during the study period. Seventy five patients (59.5%) were male. Most of the patients (44.4%) belonged to age group 21-40 year. Pulmonary TB (66.7%) was more common than extra-pulmonary TB. Multi-drug resistant TB was detected in 4 patients (3.2%). Seventy one patients (56.3%) were found to be smear positive for acid fast bacilli. First line ATD was given to 122 patients (96.8%). Out of 126 patients, 116 (92.1%) reported occurrence of at least one ADR. A higher number of ADRs were observed in male (68.3%). Change in urine color was the most common ADR (92.9%) followed by nausea and vomiting (39.7%). Further studies covering different regions of Nepal are needed to generalize the findings.